2020
DOI: 10.1186/s40001-020-00435-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of McGrath, Pentax, and Macintosh laryngoscope in normal and cervical immobilized manikin by novices: a randomized crossover trial

Abstract: Background The aim of this study was to compare tracheal intubation performance regarding the time to intubation, glottic view, difficulty, and dental click, by novices using McGrath videolaryngoscope (VL), Pentax Airway Scope (AWS) and Macintosh laryngoscope in normal and cervical immobilized manikin models. Methods Thirty-five anesthesia nurses without previous intubation experience were recruited. Participants performed endotracheal intubation in a manikin model at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…As our primary outcome, the time to DLT intubation was chosen rather than the success rate. Similar to previous studies' findings, 27-29 the investigators assumed that the success rate would increase over the number of attempts regardless of the type of laryngoscope used. That assumption can be supported by the previous studies, which did not find a significant difference in success rates between the channeled King Vision ® VL and McGrath ® VL.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As our primary outcome, the time to DLT intubation was chosen rather than the success rate. Similar to previous studies' findings, 27-29 the investigators assumed that the success rate would increase over the number of attempts regardless of the type of laryngoscope used. That assumption can be supported by the previous studies, which did not find a significant difference in success rates between the channeled King Vision ® VL and McGrath ® VL.…”
Section: Discussionsupporting
confidence: 62%
“…This is further supported by similar manikin studies, including novice participants that showed the mean times to endotracheal intubation ranged from 7.2 to 60 seconds using KVL and McGrath ® . 27,29,30,[32][33][34] The CUSUM charts are originally designed to detect minute changes from a given standard. These CUSUM charts have been adopted to assess the learning curve for specific clinical skills in the clinical setting.…”
Section: P-valuementioning
confidence: 99%
“…It is intuitive to think that DL is a difficult skill to acquire and, VL must be an easier technique for novice trainees to learn. The studies of the learning protocol in normal airway and simulated difficult airway mannequin model usually results in superiority of VL over DL (e.g., better view; shorter intubation times, higher overall success rate, less dental trauma and esophageal intubation) [207][208][209][210][211][212][213][214]. Meanwhile, practicing may improve DL and VL skill competency and the rating of overall ease of use for DL/VL.…”
Section: Learning Curve For Vs Techniquementioning
confidence: 99%
“…[22] In 2020, Kyong et al compared McGrath, AWS and Macintosh laryngoscopes for nurses with no intubation experience and found that McGrath and AWS appeared to be suitable equipment for novices to use compared to Macintosh laryngoscopes. [23] In 2021, Yuryo et al conducted a simulation study in novice doctors using Macintosh, McGrath, and AWS. They reported that McGrath and AWS were better equipment options for novice doctors than Macintosh in terms of laryngeal view and intubation success.…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing Macintosh laryngoscopy and AWS in 2018, Kyu et al reported to novice doctors that AWS provides a better laryngeal view faster and more easily and proposed including a video-laryngoscope in future intubation education [22] . In 2020, Kyong et al compared McGrath, AWS and Macintosh laryngoscopes for nurses with no intubation experience and found that McGrath and AWS appeared to be suitable equipment for novices to use compared to Macintosh laryngoscopes [23] . In 2021, Yuryo et al conducted a simulation study in novice doctors using Macintosh, McGrath, and AWS.…”
Section: Discussionmentioning
confidence: 99%